The correlation between working shifts and nurse’s motivation in the implementation of handover in the surgical documentation room - Erianti, Susi; Asfeni, Asfeni; Nurhafiza, Cut Siti (Gaceta Médica de Caracas, 2022)
Introduction: Nurses have a shift divided into morning, afternoon, and night shifts. One of the nurse’s duties is to do handovers. If the handover is not done effectively, there will be an impact on carrying out nursing care. One of the factors that influence the implementation of handovers is motivation. Poor motivation can cause the duties and roles of nurses will not to be carried out properly. This study aimed to determine the correlation between work shifts and nurses’ motivation in implementing handover.